Using Participatory Action Research to Develop a Course Module on Education for Sustainable Development in Pre-Service Chemistry Teacher Education - Mareike Burmeister; Ingo Eilks (Center for Educational Policy Studies Journal)
This paper describes the development of a course module on sustainability issues and Education for Sustainable Development in German pre-service chemistry teacher education. The module was inspired by empirical research findings about the knowledge base of student teachers. It was created and cyclically refined using Participatory Action Research. Experience gained during its three-year application will be reflected upon here, including feedback collected from student evaluation sheets. In the end, the participants responded extremely positively to the course. The student teachers stated that the module was interesting, relevant and valuable for their later profession as high school chemistry teachers. They also emphasised that they now felt more competent in the area of sustainability and ESD.